Weed Management in Rice - Dennis Calvin Odero; Matthew T. VanWeelden (EDIS)
Successful weed control is essential for economical rice production in Florida. This 6-page document discusses field sanitation and tillage, water management, and herbicides. Written by D. C. Odero and M. VanWeelden, and published by the UF/IFAS Agronomy Department, revised August 2018. http://edis.ifas.ufl.edu/wg001